Volatility spillovers in the US-China financial markets: Evidence from BEKK-GARCH model - Yang, Ting; Lau, Wee-Yeap; Bahri, Elya Nabila Abdul (Asian Journal of Economic Modelling, 2025)
This study investigates the spillover effects of volatility between the financial markets of the US and China using the BEKK-GARCH model on daily data from 4 January 2016 to 31 December 2021. The results, validated by the Wald test, reveal significant findings: First, the internationalization of the RMB has enhanced China's influence on the USD, resulting in volatility spillovers between the US dollar index and China's foreign exchange market. Second, while volatility spillovers exist between Chinese and US stock markets, the ARCH effect has weakened following the trade war. Finally, there are spillover effects between the Chinese and US bond markets, though these are less pronounced compared to the foreign exchange markets. These findings highlight the evolving nature of volatility spillovers between the US and Chinese financial markets, especially in the context of a trade war. The practical implications suggest that investors and policymakers should closely monitor these spillover effects to manage risks better and make informed decisions in an increasingly interconnected global market.